2022
DOI: 10.3390/biomimetics7020066
|View full text |Cite
|
Sign up to set email alerts
|

At the Intersection of Natural Structural Coloration and Bioengineering

Abstract: Most of us get inspired by and interact with the world around us based on visual cues such as the colors and patterns that we see. In nature, coloration takes three primary forms: pigmentary coloration, structural coloration, and bioluminescence. Typically, pigmentary and structural coloration are used by animals and plants for their survival; however, few organisms are able to capture the nearly instantaneous and visually astounding display that cephalopods (e.g., octopi, squid, and cuttlefish) exhibit. Notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 120 publications
(272 reference statements)
0
8
0
Order By: Relevance
“…(1) It is necessary to understand the design of biological materials or biological materials with dynamic and self-regulating functions from a synthetic perspective. Basic research should be carried out to better understand reflectins’ structure, self-assembly, and their tendency to form aggregates under physiological conditions [ 27 , 65 ]. (2) As membrane envelopes serve as amplifiers to the range of tunable sizes of reflectin assemblies [ 22 ], it is necessary to decipher the mechanism of how reflectins interact with cytomembranes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) It is necessary to understand the design of biological materials or biological materials with dynamic and self-regulating functions from a synthetic perspective. Basic research should be carried out to better understand reflectins’ structure, self-assembly, and their tendency to form aggregates under physiological conditions [ 27 , 65 ]. (2) As membrane envelopes serve as amplifiers to the range of tunable sizes of reflectin assemblies [ 22 ], it is necessary to decipher the mechanism of how reflectins interact with cytomembranes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, albeit not for photonic applications, the construction of reflectin assemblies in cells can establish models for wider research fields. As Atrouli et al suggested in their enlightening review, the dynamic self-assembly properties or tendency to form aggregates in vitro causes the potential surrogates of reflectins to simulate the pathogenesis of neurological disorders, because these diseases are supposed to be caused by the formation of misfolded protein aggregates [ 27 ]. Now that we can construct intracellular reflectin-based aggregates in cells, we may better understand how these misfolded proteins trigger neurological diseases under physiological conditions.…”
Section: Exploring Reflectins’ Functions and Behaviors In Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Color biomimetics in textiles encompasses diverse approaches, spanning from pigmentary to structural coloration, dynamic camouflage, and bioluminescence [9][10][11]. Pigmentary coloration refers to a photochemical process involving selective absorption of incident light, whereas in structural coloration, the process is photophysical, and color depends on how incident light interacts with the physical structure [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In our daily lives, we observe colors that are generated by two different mechanisms: structural (physical) and pigmentary (chemical) [1][2][3][4]. This paper focuses on structural colorations, which result from the interaction between light and matter.…”
Section: Introductionmentioning
confidence: 99%